2020
DOI: 10.1101/2020.06.02.20120790
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing capacity to social distance and neighborhood-level health disparities during the COVID-19 pandemic

Abstract: The COVID-19 pandemic has yielded disproportionate impacts on communities of color in New York City (NYC). Researchers have noted that social disadvantage may result in limited capacity to socially distance, and consequent disparities. Here, we investigate the role of neighborhood social disadvantage on the ability to socially distance, infections, and mortality. We combine Census Bureau and NYC open data with SARS-CoV-2 testing data using supervised dimensionality-reduction with Bayesian Weighted Quantile Sum… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 29 publications
4
37
0
Order By: Relevance
“…However, the results may not be generalizable to areas where public transportation is not available, especially in rural Louisiana. In New York, Carrion et al reported higher subway ridership among individuals who reside in neighborhoods where COVID-19 cases were higher [24]. Utility disruption is another risk factor that potentially increases the individual's risk of contracting COVID-19.…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…However, the results may not be generalizable to areas where public transportation is not available, especially in rural Louisiana. In New York, Carrion et al reported higher subway ridership among individuals who reside in neighborhoods where COVID-19 cases were higher [24]. Utility disruption is another risk factor that potentially increases the individual's risk of contracting COVID-19.…”
Section: Plos Onementioning
confidence: 99%
“…Those who reside in deprived neighborhoods, defined by low income and education, higher unemployment, and substandard living conditions, have a greater risk of poor health outcomes such as obesity, diabetes, cancer, and heart diseases [21][22][23]. Higher incidence and mortality from COVID-19 have also been observed in low-income or deprived neighborhoods [24][25][26]. A study conducted by Bilal et al reported a 36% higher incidence of COVID-19 infection in deprived neighborhoods compared to less deprived neighborhoods [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these differences reflect the living and social conditions faced by racial/ethnic minorities. For instance, institutional racism that produced residential segregation may increase the likelihood that racial/ethnic minorities live in densely populated areas with substandard and crowded housing conditions impede social distancing [ 7 , 8 ]. A recent analysis suggested that counties that are predominately black have three times the infection rate of COVID-19 compared to white majority counties [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a member of the largest public hospital network in the United States, we used resource sharing across public hospitals to balance patient load from disproportionately affected facilities in Queens and Brooklyn (Table 1 ). These were hospitals catering to communities that were affected in a disproportionate manner ( 42 ). This was done in a coordinated manner, with information regarding institution’s ICU capacity being shared in a seamless manner ( Supplement 1 , http://links.lww.com/CCX/A284 ).…”
Section: Discussionmentioning
confidence: 99%